Applicability of the Milan system for reporting salivary gland cytopathology: A single Brazilian institution experience - Tokunaga, Juliana Akemi Dornellas; de Peres, Eduardo Augusto Souza; Camilo-Junior, Deolino João; Xavier-Junior, José Cândido Caldeira [UNESP] (Wiley, 2023)
Introduction: The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) emerged in 2015 as an attempt to establish protocols for a most appropriate follow-up and treatment of patients with salivary gland lesions. Through fine needle aspiration (FNA), a safe and minimally invasive way to obtain cytological samples, the lesion is classified into one of the six categories, which have different risks of malignancy (ROM) and, therefore, different management. Materials and Methods: FNA cytology procedures performed between January 2016 and June 2020 (54 months) at the Pathology Institute of Araçatuba, São Paulo, Brazil, were analyzed by two pathologists with more than 5 years of experience. The ROM for each of the diagnostic categories was determines and compared with the ROM expected by the MSRSGC. Results: A total of 99 FNA of salivary gland lesions were reviewed and retrospectively categorized. Histopathological follow-up was available for 58 of 96 patients (60.42%). The patients age ranged from 23 to 98 years with the mean of 58.15 ± 15.29 years. The parotid gland was the most affected (81.82%). The average size of the lesions was 2.59 cm. The ROM for each category was 16.67%, 0%, 0%, 2.86%, 50%, 100%, 100%, respectively. Conclusion: This is the first Brazilian study describing the application of the MSRSGC in the routine of a private Laboratory out of a cancer center service. Therefore, it is an effective method in the classification of salivary gland lesions, when associated with the MSRSGC, to determine the ROM and its appropriate treatment.
Keywords: cytology; fine-needle aspiration; salivary gland neoplasms